Targeting JAK2/STAT3, NLRP3/Caspase-1, and PK2/PKR2 Pathways with Arbutin Ameliorates Lead Acetate-Induced Testicular Injury in Rats - Hany H. Arab; Shuruq E. Alsufyani; Ahmed M. Ashour; Amany M. Gad; Alzahraa A. Elhemiely; Mohamed H. A. Gadelmawla; Marwa Ahmed Mahmoud; Ali Khames (MDPI AG, 2024)
The reproductive system of males is adversely impacted by lead (Pb), a toxic heavy metal. The present study examined arbutin, a promising hydroquinone glycoside, for its potential ameliorative impact against Pb-induced testicular impairment in rats. The testicular injury was induced by the intraperitoneal administration of Pb acetate (20 mg/kg/day) for 10 consecutive days. Thirty-six rats were divided into six experimental groups (n = 6 per group): control, control treated with oral arbutin (250 mg/kg), control treated with intraperitoneal arbutin (75 mg/kg), untreated Pb, Pb treated with oral arbutin, and Pb treated with intraperitoneal arbutin. The treatments were administered daily for 10 days. Arbutin was administered by the oral and intraperitoneal routes to compare the efficacy of both routes in mitigating Pb acetate-induced testicular dysfunction. The current data revealed that both oral and intraperitoneal administration of arbutin significantly enhanced serum testosterone and sperm count/motility, indicating the amelioration of testicular dysfunction. In tandem, both routes lowered testicular histopathological aberrations and Johnsen's damage scores. These favorable outcomes were driven by dampening testicular oxidative stress, evidenced by lowered lipid peroxidation and increased glutathione and catalase antioxidants. Moreover, arbutin lowered testicular p-JAK2 and p-STAT3 levels, confirming the inhibition of the JAK2/STAT3 pro-inflammatory pathway. In tandem, arbutin suppressed the testicular NLRP3/caspase-1/NF-B axis and augmented the cytoprotective PK2/PKR2 pathway. Notably, intraperitoneal arbutin at a lower dose prompted a more pronounced mitigation of Pb-induced testicular dysfunction compared to oral administration. In conclusion, arbutin ameliorates Pb-evoked testicular damage by stimulating testicular antioxidants and the PK2/PKR2 pathway and inhibiting the JAK2/STAT3 and NLRP3/caspase-1 pro-inflammatory pathways. Hence, arbutin may be used as an adjunct agent for mitigating Pb-induced testicular impairment.